Changing Times: Altering Establishment Spacing, Harvesting Frequency, and Harvesting Machines to Promote Increased Sawtimber Volumes - Daniel, Marissa “Jo”; Gallagher, Tom; Mitchell, Dana; McDonald, Timothy; Via, Brian (Frontiers in Energy Research, 2018)
Today’s landowners are faced with important decisions when establishing loblolly pine plantations in the Southeastern part of the United States with regards to planting dimensions and forest management techniques. Although recent studies are beginning to demonstrate the need for change from the old practices, suppressed biomass markets and prices are hindering the transition. This paper provided readers with an informational overview of the benefits of: incorporating an additional thinning regime for biomass, using alternate spacing methods such as FlexstandsTM and rectangularity, and using small-scale harvesting machines for conducting initial thinning’s. The overview was supported with both a field study as well as a modeling tool which verified using one or all of the above-mentioned techniques to increase total harvest volumes while minimizing residual stand damage. The modeling tool determined that final sawtimber volumes were increased by a minimum of 15 tons per acre using one or more of the above techniques. When expanding this volume out to 20 acres, the minimum tract size harvested in the southeast using convention equipment, landowners could easily recover any losses incurred from the suppressed biomass markets minimizing overall risk and promoting the use of these alternative techniques.